GREEN REVERSE-PHASE – HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY APPROACH FOR STABILITY-INDICATING SIMULTANEOUS QUANTIFICATION OF DORAVIRINE, LAMIVUDINE, AND TENOFOVIR IN BULK AND DOSAGE FORMS - SUBHRANSHU PANDA; SIRISHA GORANTLA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: A simple, accurate, and validated reverse-phase high-performance liquid chromatography (HPLC) method was developed for the simultaneous estimation of doravirine, lamivudine, and tenofovir in pharmaceutical formulations. Methods: Chromatographic separation was achieved using a Zorbax Eclipse Plus C18 column (2.1×150 mm, 5 μm) with a mobile phase composed of 0.01 M potassium phosphate buffer (pH adjusted with orthophosphoric acid) and HPLC-grade acetonitrile, delivered at a flow rate of 1 mL/min. Detection was performed at 244 nm. Results: The method yielded sharp, well-resolved peaks with retention times of 2.195 min for doravirine, 2.715 min for lamivudine, and 3.676 min for tenofovir. A peak resolution of 4.4 confirmed efficient separation. The method exhibited excellent linearity with a correlation coefficient (R²) of 0.9999 across concentration ranges of 2.515 μg/mL for doravirine and 7.545 μg/mL for both lamivudine and tenofovir. Accuracy was confirmed through recovery studies, yielding 100.02% for doravirine, 100.09% for lamivudine, and 99.98% for tenofovir. The method also demonstrated high sensitivity, with limits of detection of 0.01 μg/mL for doravirine and 0.11 μg/mL for both lamivudine and tenofovir. The respective limits of quantification were 0.04 μg/mL, 0.32 μg/mL, and 0.34 μg/mL. The regression equations derived were as follows: y=30936x +3374.3 for doravirine, y=29559x+889.66 for lamivudine, and y=29768x+3035.2 for tenofovir. Conclusion: In addition to its strong analytical performance, the method was evaluated using the AGREE metric for green analytical chemistry compliance. Despite the use of acetonitrile, it achieved an AGREE score of 0.73, indicating good environmental compatibility due to minimal solvent consumption, energy efficiency, and avoidance of derivatization. This method – with its short runtime, high accuracy, cost-effectiveness, and environmentally responsible design – is highly suitable for routine quality control and stability studies of antiretroviral pharmaceutical formulations.